Clinical Presentation Resembling Mucosal Disease Associated with 'HoBi'‐like Pestivirus in a Field Outbreak. Issue 1 (16th April 2014) - Weber, M. N.; Mósena, A. C. S.; Simões, S. V. D.; Almeida, L. L.; Pessoa, C. R. M.; Budaszewski, R. F.; Silva, T. R.; Ridpath, J. F.; Riet‐Correa, F.; Driemeier, D.; Canal, C. W.
Summary: The genus Pestivirus of the family Flaviviridae consists of four recognized species: Bovine viral diarrhoea virus 1 (BVDV‐1), Bovine viral diarrhoea virus 2 (BVDV‐2), Classical swine fever virus (CSFV) and Border disease virus (BDV). Recently, atypical pestiviruses ('HoBi'‐like pestiviruses) were identified in batches of contaminated foetal calf serum and in naturally infected cattle with and without clinical symptoms. Here, we describe the first report of a mucosal disease‐like clinical presentation (MD) associated with a 'HoBi'‐like pestivirus occurring in a cattle herd. The outbreak was investigated using immunohistochemistry, antibody detection, viral isolation and RT‐PCR. The sequence and phylogenetic analysis of 5′NCR, N pro and E2 regions of the RT‐PCR positive samples showed that four different 'HoBi'‐like strains were circulating in the herd. The main clinical signs and lesions were observed in the respiratory and digestive systems, but skin lesions and corneal opacity were also observed. MD characteristic lesions and a pestivirus with cytopathic biotype were detected in one calf. The present study is the first report of a MD like presentation associated with natural infection with 'HoBi'‐like pestivirus. This report describes the clinical signs and provides a pathologic framework of an outbreak associated with at least two different 'HoBi'‐like strains. Based on these observations, it appears that these atypical pestiviruses are most likely underdiagnosed in Brazilian cattle.